Peran Pelatihan Karyawan dan Lingkungan Kerja dalam Membangun Budaya Organisasi pada Industri Perhotelan di Batam - Muhammad Donal Mon; Noerul Aini (Universitas Batanghari Jambi, 2026)
This study aims to analyze the extent to which employee training and the work environment influence organizational culture in the hospitality sector. A quantitative approach was used, distributing questionnaires to 200 respondents working in various hotels in Batam. The results indicate that employee training, performance management, and the work environment significantly influence organizational culture in the hospitality industry in Batam.